2022
DOI: 10.3390/ijms23095022
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-20a-5p Downregulation by Atorvastatin: A Potential Mechanism Involved in Lipid-Lowering Therapy

Abstract: The treatment of hypercholesterolemia is mainly based on statins. However, the response to pharmacological therapy shows high inter-individual variability, resulting in variable effects in both lipid lowering and risk reduction. Thus, a better understanding of the lipid-lowering mechanisms and response variability at the molecular level is required. Previously, we demonstrated a deregulation of the microRNA expression profile in HepG2 cells treated for 24 h with atorvastatin, using a microarray platform. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“… 55 , 56 A study reported that the downregulation of hsa-mir-20a-5p by atorvastatin can increase the low-density lipoprotein receptor (LDLR) mRNA and protein expression in HepG2 cells, while the overexpression of has-mir-20a-5p can reduce the LDLR mRNA and protein expression. 57 In another study on COAD, hsa-mir-186-5p was described as a tumor suppressive factor that inhibits the SMAD6 and SMAD7 expression, thereby regulating the tumor growth factor-β signaling pathway. 58 …”
Section: Discussionmentioning
confidence: 99%
“… 55 , 56 A study reported that the downregulation of hsa-mir-20a-5p by atorvastatin can increase the low-density lipoprotein receptor (LDLR) mRNA and protein expression in HepG2 cells, while the overexpression of has-mir-20a-5p can reduce the LDLR mRNA and protein expression. 57 In another study on COAD, hsa-mir-186-5p was described as a tumor suppressive factor that inhibits the SMAD6 and SMAD7 expression, thereby regulating the tumor growth factor-β signaling pathway. 58 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that downregulation of hsa-circ-0107593 promotes the osteogenic differentiation of hADSCs through miR-20a-5p/SMAD6 signaling (51). Atorvastatin may be involved in lipid-lowering therapy by downregulating microRNA-20a-5p (52). hsa-miR-20a-5p attenuates allergic in ammation in HMC-1 cells by targeting HDAC4 (53).…”
Section: Discussionmentioning
confidence: 99%